Patient experiences with technology enabled care across healthcare settings- a systematic review - Ann-Chatrin Linqvist Leonardsen; Camilla Hardeland; Ann Karin Helgesen; Vigdis A. Grøndahl (BMC, 2020)
Abstract Background Healthcare services are facing extensive challenges due to the increased proportion of elderly persons and persons with chronic disease. Technology enabled care (TEC) is a collective term for telecare, telehealth, telemedicine, mobile (m)-, digital- and electronic (e) health services. TEC is increasingly seen as a solution to many of the challenges facing the health sector. Patient perspectives may provide a useful evaluation tool for new healthcare technologies that have limited clinical data to support their effectiveness. More studies need to be done to better understand the acceptance of technology in healthcare. This review aim to summarize empirical studies exploring patient experiences with TEC. Findings in this study can be used to better understand what is needed to develop, implement and improve such services. Methods Systematic searches were conducted in the Pubmed, Psycinfo, Cinahl, Embase, Cochrane systematic reviews and Cochrane clinical trials databases. These studies were systematically reviewed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, subjected to quality appraisals using the Critical Appraisal Skills Program (CASP), and synthesized via integrative analysis. Results After removal of duplicates, languages other than English, and non-scientific records, 4087 titles and abstracts were screened. After assessment against inclusion and exclusion criteria, 69 records were screened in full-text, and underwent quality appraisal. 21 records were included in the integrative analysis. Patients' experiences with TEC related to 1) technological features, namely functionality and appearance, and 2) evolving independence, namely empowerment, autonomy and security. Technological challenges lead to frustrations and negative experiences, while a stigmatizing appearance lead to patients not using the solution. Through the use of TECs, patients felt more empowered, learning about their condition, increasing awareness to their symptoms and treatment, and feeling more safe and self-efficient. Patient participation was seen as a central aspect of the development of the TECT, as well as when using it. Conclusion This review deepens the understanding of patients' experiences with technology enabled care solutions. Patients' experiences not only relate to the practical/technical element of the device or solution, but to how this impact on their everyday life. Patient participation in development and planned use of such solutions should be considered an integral part in healthcare quality initiatives.